Synergistic Polarization Engineering on Bulk and Surface for Boosting CO2 Photoreduction. (2nd July 2021) - Liu, Lizhen; Huang, Hongwei; Chen, Zhensheng; Yu, Hongjian; Wang, Keyang; Huang, Jindi; Yu, Han; Zhang, Yihe
Abstract: Sluggish charge kinetics and low CO2 affinity seriously inhibit CO2 photoreduction. Herein, the synchronous promotion of charge separation and CO2 affinity of Bi4 Ti3 O12 is realized by coupling corona poling and surface I‐grafting. Corona poling enhances ferroelectric polarization of Bi4 Ti3 O12 by aligning the domains direction, which profoundly promotes charge transfer along opposite directions across bulk. Surface I‐grafting forms a surface local electric field for further separating charge carriers and provides abundant active sites to enhance CO2 adsorption. The two modifications cooperatively further increase the ferroelectric polarization of Bi4 Ti3 O12, which maximize the separation efficiency of photogenerated charges, resulting in an enhanced CO production rate of 15.1 μmol g −1  h −1 (nearly 9 times) with no sacrificial agents or cocatalysts. This work discloses that ferroelectric polarization and surface ion grafting can promote CO2 photoreduction in a synergistic way. Abstract : Synergistic polarization engineering on bulk and surface of Bi4 Ti3 O12 is realized by coupling corona poling and surface I‐grafting, which strengthen ferroelectric polarization for facilitating the separation and transfer of photogenerated charge carriers and enrich the reactive sites, largely improving the photocatalytic activity for reducing CO2 into CO.